Research trends and geographical distribution of mammalian carnivores in Portugal (SW Europe) - Bencatel, Joana (2019)
Information regarding species’ status at a regional scale is instrumental for effective conservation planning. Some regions of southwestern Europe, such as Portugal, albeit included in the Mediterranean biodiversity hotspot, lack a detailed assessment of the distribution patterns of several taxonomic groups, such as carnivores. Moreover, information is scattered, often unreliable and biased towards some species or regions. This study aimed at reviewing the existing knowledge on mammalian terrestrial carnivores in Portugal, to analyse research trends, update the species checklist and assess their historical and current distribution patterns. We conducted a comprehensive review of 755 scientific studies to analyse several publication metrics and compiled 20,189 presence records of all mammalian terrestrial carnivores occurring in Portugal since historical times to evaluate their distribution patterns. Carnivore research in Portugal began in the 18th century, with a recent boost in the mid- 1990s, and has been biased towards certain research topics and regionally threatened species. There are 15 extant species in Portugal, with nine occurring across the country, six showing a more limited range, as well as one additional species currently locally extinct (Ursus arctos). Over the last decades, the distribution ranges of seven species apparently remained stable, two expanded, two contracted, and three showed unclear trends. The presence of a new invasive carnivore, the raccoon (Procyon lotor), is also documented here. This study illustrates the relevance of a comprehensive analysis of non-systematic data to assess the historic and current status of mammalian terrestrial carnivores at a national level, and to identify knowledge gaps and research priorities.